Response of calves persistently infected with noncytopathic bovine viral diarrhea virus (BVDV) subtype 1b after vaccination with heterologous BVDV strains in modified live virus vaccines and Mannheimia haemolytica bacterin-toxoid - Fulton, Robert W. (Vaccine, 2003)
Seronegative persistently infected (PI) calves with bovine viral diarrhea virus (BVDV) subtype 1b were vaccinated with each of four modified live virus (MLV) BVDV vaccines and a Mannheimia haemolytica bacterin-toxoid. Nasal swabs and peripheral blood leukocytes (PBL) were collected for virus isolation and serums were collected after vaccination and tested for BVDV1a, BVDV1b, BVDV2, bovine herpesvirus-1 (BHV-1), bovine parainfluenza-3 virus (PI-3V), and bovine respiratory syncytial virus (BRSV) antibodies. M. haemolytica and Pasteurella multocida antibodies were detected using ELISA procedures. None of the PI calves developed mucosal disease (MD) after MLV vaccination. None of the BVDV PI calves seroconverted to BVDV1b after MLV vaccination. Calves receiving MLV vaccines seroconverted to the respective type/subtype in the vaccine. Calves receiving a MLV vaccine with noncytopathic (NCP) BVDV1 (subtype not designated) did not seroconvert to BVDV1a, BVDV1b, or BVDV2. The PI calves were positive for BVDV subtype 1b, in the PBL and nasal swabs throughout the study. Calves receiving each of three vaccines with known BVDV1a strains had BVDV1a positive samples after vaccination, in some but not all calves, up to Day 28. The PI BVDV1b calves did not respond with increased M. haemolytica antibodies after vaccination compared to BVDV negative calves receiving the same M. haemolytica vaccine.